Environmental management of companies in the oil and gas markets based on AI for sustainable development: An international review - Chutcheva, Yuliya V.; Kuprianova, Lyudmila M.; Seregina, Antonina A.; Kukushkin, Sergey N. (Frontiers in Environmental Science, 2022)
The purpose of the article is to study the current international experience and determine the prospects for improving the environmental management of companies in the oil and gas markets based on AI in the interests of sustainable development. Relying on variation analysis and correlation analysis methods, it has been substantiated that environmental management have significant impact on companies from the perspective of social LCA, which has an impact on the competitive ability of companies. Relying on the IPAT-method, it has been proven that technology is a key factor which determines this impact. As a result, it has been proved on the example of the case experience of the largest energy companies in Russia in 2022 that the environmental management of oil and gas companies creates advantages not only for the environment but also for financial efficiency and stability (break-even operation) of these companies (implementation of SDG 8). Using the example of the international experience of energy companies (from the UAE, Sweden, the UK, the USA and Japan), it has been proved that AI can play a much greater role in the oil and gas markets, contributing not only to ensuring a deficit-free energy economy (the implementation of SDG 7) but also to environmental protection (the implementation of SDGs 13-15). The best practices of using AI in each selected sector of the oil and gas industry were studied and a quantitative and qualitative assessment of the benefits of AI was carried out. Thirdly, the most promising use of AI in the sector of environmental management for environmental economics and management is substantiated. It is proven that the options for environmental management can be different and specific to a particular object. Thanks to the results obtained in the course of the study, a systematic view of the prospects for the sustainable development of oil and gas markets has been formed, and the importance of AI for this process has been demonstrated. The theoretical significance of the study consists in expanding the existing understanding of the use of AI in the practice of environmental management of energy companies and clarifying its contribution to the implementation of the SDGs.